PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Ainul Marhamah Hasibuan; Siti Aisyah Hasibuan; Dinda Wirly Dawani (JURNAL TEMATIK, 2020)
This study aims to see the increase in problem-solving abilities using learning tools that have been developed and use a realistic mathematics approach. This research is a developmental research. This study uses trials of problem-based learning tools to see the effectiveness of improving students' problem-solving abilities. Students' mathematical problem solving abilities using realistic mathematics learning-based learning tools developed in the first trial obtained an average posttest score of 72%, and increased in the second trial with an average posttest score of 92%. Based on the results of the study, it is suggested that mathematics teachers strive for learning mathematics using quality learning tools and especially by using realistic mathematics approach-based learning